2006
DOI: 10.1093/eurheartj/ehi814
|View full text |Cite
|
Sign up to set email alerts
|

Left intraventricular myocardial deformation dyssynchrony identifies responders to cardiac resynchronization therapy in patients with heart failure

Abstract: Patients with chronic HF should undergo ultrasound evaluation to quantify dyssynchrony of LV myocardial deformation, which would help identifying CRT responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 17 publications
3
68
1
2
Order By: Relevance
“…Patients were classi ed as responders if their LVEF increased by at least 20 , and/or the LVESV decreased by at least 15 with respect to baseline variations were considered as relative values . Patients were de ned as non-responders if they did not reach both of the above pre-speci ed echocardiographic changes 8 .…”
Section: Echocardiographic Evaluationmentioning
confidence: 99%
“…Patients were classi ed as responders if their LVEF increased by at least 20 , and/or the LVESV decreased by at least 15 with respect to baseline variations were considered as relative values . Patients were de ned as non-responders if they did not reach both of the above pre-speci ed echocardiographic changes 8 .…”
Section: Echocardiographic Evaluationmentioning
confidence: 99%
“…The initial results of dyssynchrony assessment using strain imaging have been conflicting, mainly regarding correlation with reverse remodelling (42,43). In a recent study, TDI Ts-SD in a 12-segment model predicted reverse remodelling with a sensitivity of 93% and a specificity of 73%, but correlation with strain was poor (44).…”
Section: Strain Strain Rate and Speckle Trackingmentioning
confidence: 99%
“…54 A delay Ͼ130 ms in time to peak radial strain in the anteroseptal and inferolateral walls predicted a short-term increase in stroke volume, 47 and the standard deviation in time to peak longitudinal strain among 12 basal and mid segments predicted reverse remodeling 6 months after CRT. 49 Using 2-dimensional speckle tracking, a delay Ͼ130 ms in time to peak systolic radial strain among 6 mid segments in the parasternal short-axis view (Figure 7) predicted increase in LVEF Ͼ15% with a sensitivity of 89% and a specificity of 83% at 8 months after CRT. 48 In contrast to these positive results, Yu and colleagues reported that standard deviation in time to peak systolic TDI-derived strain in 12 segments did not predict the response to CRT in 2 studies (a first study in 55 patients 42 and a second in 256 patients 43 ).…”
Section: Strain Imagingmentioning
confidence: 99%